Research on the Impact of Artificial Intelligence on Employment Quality - He Mengchao (SHS Web of Conferences)
This paper analyses the effect of the development of artificial intelligence (AI) on employment quality according to the panel data of 300 cities in China from 2010 to 2020. The research finds the development of AI significantly improves employment quality, especially in terms of employability, employment security, and employment remuneration. For everyone-standard-deviation increase in AI technology density, the wage premium for technical jobs is 1.8%, but the real wages of repetitive jobs decrease by 0.6%. However, the effect of AI on the employment situation is negative, which may be due to the increase in the unemployment rate. For every 1-unit increase in the density of industrial robots per thousand people, employment in the manufacturing industry decreases by 0.18%, and this effect shows an accelerating feature in the later stage of technology diffusion. Based on this, this paper proposes policy recommendations to increase investment in education and training and improve the social security system.